Association of a single nucleotide polymorphism of RANK gene with blood pressure in Spanish women. Issue 40 (2nd October 2020) - Pertusa, Clara; Tarín, Juan J.; Cano, Antonio; García-Pérez, Miguel Angel
Abstract : Abstract: In addition to governing key functions in bone metabolism and the immune system, the RANK/RANKL/OPG system plays a role in the vascular system, particularly in vascular calcification and atherosclerosis. Given that these 2 phenotypes are considered a major cause of high blood pressure (BP), in this study we analyzed the association of SNPs in RANK and OPG genes with blood pressure. An observational study was conducted of 2 SNPs in the RANK gene (rs884205 and rs78326403) and 1 in the OPG gene (rs4876869) with systolic (SBP) and diastolic blood pressure (DBP) in a cohort of 695 women. Data analysis revealed a statistically significant association between the SNP rs884205 and BP pressure (SBP and DBP). Analyzing this relationship by the dominant inheritance model for this SNP (allele risk: A), women of the AA/AC genotype showed higher BP than women of the CC genotype, both for SBP ( P = .001) and for DBP ( P = .003), and these associations both surpassed the Bonferroni threshold for multiple comparisons. Multivariate regression analysis including known predictors of BP as independent variables was performed to evaluate the strength of this association, which in the case of the SNP rs884205 of the RANK gene remained statistically significant after adjustment for both SBP ( P = .0006) and DBP ( P = .005), demonstrating the key role of this SNP in BP. We report a robust association between the SNP rs884205 in RANK gene and BP in women, and this SNP is validated as a candidate in cardiovascular risk studies.